"Put Your Hands Up": How Joint Attention Is Initiated Between Blind Children And Their Sighted Peers - Morrison, Cecily; Grayson, Martin (CHI Conference on Human Machine Interaction, 2025)
Initiating joint attention (JA) is a fundamental first step in social interactions. In sighted individuals, it relies predominantly on visual cues, such as gaze and hand gestures. These features can reduce opportunities for blind and visually impaired (BVI) and sighted people to interact. Understanding the strategies to navigate these challenges is necessary to develop technology that can facilitate more inclusive JA. To address this, we conducted a longitudinal case study of five children with mixed visual abilities engaging in activities rich with JA opportunities. In a teacher-led classroom, the children experimented with the use of an AI-powered headset designed to support BVI people in social situations. Interaction analysis established that situational complexity affects the children’s responses to initiation attempts. Furthermore, the headset adds to this complexity, affecting the frequency and reactions to attempts to initiate JA. The findings informed the creation of a JA initiation framework and suggestions for future design.